El mundo de la lógica y la lógica del mundo: logos, naturaleza y espíritu en Hegel (2013)
This article tries to examine the hegelian sense of rationality, which fundament is the speculative concept. This allows the intellection of what “philosophical sciences” means in the System of Science exposed in the Encyclopedia. Consequently this text tries to understand also the way how the three final syllogisms of Encyclopedia must be explained.